Introduction to recent developments and future opportunities for polymer nanocomposite membranes - Muhammad Khusairy, Bakri; Md. Rezaur, Rahman; Norazzlina, M.Sa'don (Woodhead Publishing is an imprint of Elsevier, 2025)
The process of urbanization and industrialization has resulted in a rapid increase in the usage of water (Cheng et al., 2023), hence worsening the worldwide water problems. Water pollution has a significant impact on several parts of the biosphere, such as humans, the atmosphere, aquatic habitats, and other connected organisms. This impact results in considerable expenses (Abdali et al., 2017). Contaminants from diverse sources, such as household trash and industry operations, including paper making, agriculture, and textile production, continuously degrade water quality. Although there have been significant gains, it is still crucial for the world to make coordinated efforts to ensure that everyone has access to safe and clean water (Hazarika et al., 2023).